Estimation of the state of human erythrocytes surface in the hypertonic electrolyte medium. 2. State of external pre-membranous layers - Kuleshova, L. G. (Biophysical Bulletin, 2018)
Surface state of human erythrocytes in NaCI hypertonic medium of electrolyte was studied in the work by the methods of spectrophotometry, optic light and phase-contrast microscopy. It was established that human erythrocytes manifested significant hypertonic stability. However due to dehydration processes the erythrocytes transformation occurs with considerable change of the shape of cellular surface, that, in its turn, is accompanied by a partial destruction of external pre-membranous layers (glicocalix) and elimination of glycoproteins into extracellular medium.